2017
DOI: 10.1097/md.0000000000007520
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis due to Streptococcus pneumoniae associated with secondary hemophagocytic lymphohistiocytosis in a splenectomized patient for spherocytosis

Abstract: Rationale:Hemophagocytic lymphohistiocytosis (HLH) is a syndrome that is characterized by an inappropriate hyperinflammatory immune response – primary, as a consequence of a genetic defect of NK cells and cytotoxic T lymphocytes or – secondary, in the progression of infections, rheumatic or autoimmune diseases, malignancies or metabolic diseases.Patient concerns:We present the case of a secondary HLH due to Streptococcus pneumoniae infection in a splenectomised patient for spherocytosis, a 37-year-old patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…[ 20,48 ] Consequently, the sensitivity and specificity of pH would need to be evaluated clinically, especially compared to inflammation from aseptic loosening (which is also interesting but would be treated differently). [ 13,49 ] Moreover, the threshold and required resolution would depend upon the application, for example in early screening versus confirmation or monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20,48 ] Consequently, the sensitivity and specificity of pH would need to be evaluated clinically, especially compared to inflammation from aseptic loosening (which is also interesting but would be treated differently). [ 13,49 ] Moreover, the threshold and required resolution would depend upon the application, for example in early screening versus confirmation or monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] The current standard of care involves arthrocentesis when an infection is suspected, where the joint is aspirated using a syringe to collect synovial fluid from the joint capsule and analyzed for white blood cell count and differential, crystals, Gram stain, and culture. [ 12,13 ] In addition, the synovial fluid contains infection biomarkers such as glucose, [ 14 ] low pH/high lactate concentrations, [ 15 ] C‐reactive protein, [ 16,17 ] interleukins, [ 18 ] interferon‐γ, [ 10 ] α defensin, [ 16 ] and cathelicidin [ 19 ] which can be useful for the diagnosis of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the incidence of childhood HLH caused by bacterial infection accounts for about 6% of all IAHS cases [ 3 ], including Streptococcus pneumonia , Mycobacterium tuberculosis , Leptospira, Brucella, and group B hemolytic streptococcus, Streptococcus suis , Haemophilus influenzae , Klebsiella pneumonia , Staphylococcus aureus , Mycobacterium bovis , Salmonella typhimurium , Mycoplasma pneumonia , Q fever, Jungle typhus, etc. [ 4 9 ]. There is no report of S. intermedius brain abscess-induced HLH mentioned in literature before.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported bacterial infection-associated HLH [7], including Mycoplasma pneumoniae [8,9], Listeria monocytogenes [10], Leptospira [11], Brucella [12], group B streptococcus [13], and Coxiella burnetii [14]. Secondary HLH caused by S. pneumococcus has been previously described in adults after splenectomy or with primary immunodeficiency [15,16]. However, there are very few cases of secondary HLH complicated with IPD in previously healthy children.…”
Section: Discussionmentioning
confidence: 99%